The virtual food system: Innovative models and experiential feedback in technologies for winemaking, the cereals chain, food packaging and eco-designed starter production. (April 2018) - Aceves Lara, César Arturo; Athès, Violaine; Buche, Patrice; Della Valle, Guy; Farines, Vincent; Fonseca, Fernanda; Guillard, Valérie; Kansou, Kamal; Kristiawan, Magdalena; Monclus, Vincent; Mouret, Jean-Roch; Ndiaye, Amadou; et al.
Abstract: This article presents an overview of five use-cases that illustrate food-system modeling approaches, most of them combining quantitative and qualitative methods. The cases deal with issues as diverse as: the modeling of winemaking fermentation; the choice of a food packaging material; the design of solid foam cereal products; argumentation modeling to support multistakeholder decision-making, and the control of freeze-drying for eco-design purposes. They tackle several challenges to modeling and knowledge engineering in food systems: capitalizing data and knowledge; structuring a shared vocabulary and domain knowledge in an ontology; formalizing viewpoints and contradictions from food-related debates; supporting multi-criteria decision-making. Highlights: The paper proposes an overview of five use cases to illustrate a variety of modeling approaches for food systems. Applications in the fields of winemaking, food packaging, cereals, public decision, and freeze-drying are presented. Methods go from knowledge integration to multi-criteria decision through process simulation and life cycle assessment. A synthesis of the issues, methods, results and feedbacks from the use cases is provided.